Implementation of BPOM's Authority In Issuing Distribution Permits and Supervising Skincare Products - Cordelia, Anastasia; Loren, Celine; Matulandi, Sabina Abigail (Dinasti Research, 2025)
This research examines how the Food and Drug Supervisory Agency (BPOM) carries out its authority to give distribution permits and supervise the sale of skincare products in Indonesia. This study applies a juridical-normative approach, applying relevant laws and secondary data from official BPOM documents and reports. The research results indicate that the skincare distribution permits are explicitly regulated in Law (Undang-Undang) No. 36 of 2009 concerning Health, and Law (Undang-Undang) No. 8 of 1999 concerning Consumer Protection, and BPOM Regulation No. 12 of 2020 concerning Procedures for Submitting Cosmetic Notifications. The process of obtaining approval of a product involves submitting a product notification, undergoing BPOM evaluation, obtaining a notification number, and fulfilling the post-approval requirements. From an administrative law perspective, the procedure shows the principles of good governance, whereas from a commercial law perspective, a distribution permit serves as a legal requirement for selling products. In practice this process still encounters many significant challenges, often leading to the widespread use of illegal products without permits. The discovery of harmful skincare and cosmetics valued at billions of rupiah and the difficulty of monitoring online sales across platforms illustrate major regulatory problems. Therefore, providing effective legal protection for consumers in Indonesia. Therefore, stronger supervision and cooperation between sectors are needed to give better legal protection for consumers in Indonesia.